2014
DOI: 10.1073/pnas.1423314112
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Pseudomonas aeruginosa transamidosome reveals unique aspects of bacterial tRNA-dependent asparagine biosynthesis

Abstract: Many prokaryotes lack a tRNA synthetase to attach asparagine to its cognate tRNAAsn, and instead synthesize asparagine from tRNAAsn-bound aspartate. This conversion involves two enzymes: a nondiscriminating aspartyl-tRNA synthetase (ND-AspRS) that forms Asp-tRNAAsn, and a heterotrimeric amidotransferase GatCAB that amidates Asp-tRNAAsn to form Asn-tRNAAsn for use in protein synthesis. ND-AspRS, GatCAB, and tRNAAsn may assemble in an ∼400-kDa complex, known as the Asn-transamidosome, which couples the two steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…(B) covariance‐assisted fragment‐assembly model of residues 72‐167. (C) The crystal structure of Primosomal Replication Protein N Klebsiella pneumonia (PDB code 4apv; ) D) the OB fold from subunit A of the structure of Pseudomonas aeruginosa Glutamyl‐tRNA(Gln) Amidotransferase (PDB code 4wj3; ). [Color figure can be viewed in the online issue, which is available at http://wileyonlinelibrary.com.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) covariance‐assisted fragment‐assembly model of residues 72‐167. (C) The crystal structure of Primosomal Replication Protein N Klebsiella pneumonia (PDB code 4apv; ) D) the OB fold from subunit A of the structure of Pseudomonas aeruginosa Glutamyl‐tRNA(Gln) Amidotransferase (PDB code 4wj3; ). [Color figure can be viewed in the online issue, which is available at http://wileyonlinelibrary.com.…”
Section: Resultsmentioning
confidence: 99%
“…This is not seen in the top DALI match [Fig. (C)], but is seen in the structure of the ligase domain of the asparagine transamidosome from Pseudomonas aeruginosa [PDB code 4wj3; Fig. (D)] which matched the model with a DALI score of 6.6.…”
Section: Resultsmentioning
confidence: 99%
“…Using Phyre2 23 we found that the closest 3D homologs of Tse8 are the Stenotrophomonas maltophilia Peptide amidase (Pam) 24 (sequence identity 29%), the Staphylococcus aureus Gln-tRNA(Gln) transamidosome subunit A (GatA) 25 (sequence identity 20%), the P. aeruginosa Asn-tRNA(Asn) transamidosome subunit A (GatA) 26 (sequence identity 25%), the Flavobacterium sp. 6-aminohexanoate cyclic dimer hydrolase (NylA) 27 (sequence identity 24%), the Bradyrhizobium japonicum malonamidase E2 (MAE2) 28 (sequence identity 25%), the Pseudomonas sp.…”
Section: Tradis Identifies Known and Novel H1-t6ss Toxin-immunity Pairsmentioning
confidence: 99%
“…The structure of the P. aeruginosa GatCAB transamidosome reveals it to be a symmetric complex comprising ND-AspRS, GatCAB, and tRNA Asn in a 2:2:2 stoichiometry 26 (as represented in Extended Data Fig. 8a).…”
Section: Tradis Identifies Known and Novel H1-t6ss Toxin-immunity Pairsmentioning
confidence: 99%
“…5). The transamidosome is a three protein complex (GatCAB) that is essential for the production of correctly charged tRNA in bacteria via the transfer of an ammonia from gutamine to acidic amino acid-charged tRNA (21). Deamination occurs in the active site of an amidase (GatA).…”
Section: Atze Is a 1-carboxybiuret Hydrolase -mentioning
confidence: 99%